2011
DOI: 10.1007/s13238-011-1061-y
|View full text |Cite
|
Sign up to set email alerts
|

Interactomic study on interaction between lipid droplets and mitochondria

Abstract: An increasing body of evidence shows that the lipid droplet, a neutral lipid storage organelle, plays a role in lipid metabolism and energy homeostasis through its interaction with mitochondria. However, the cellular functions and molecular mechanisms of the interaction remain ambiguous. Here we present data from transmission electron microscopy, fluorescence imaging, and reconstitution assays, demonstrating that lipid droplets physically contact mitochondria in vivo and in vitro. Using a bimolecular fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
139
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 31 publications
6
139
0
Order By: Relevance
“…It has been proposed that mitochondria, peroxisomes, ER membranes, and endosomes may be physically associated with LDs (5,34) or may even be continuous with LDs in terms of phospholipid membrane topology (35). Recently, we conducted an interactomic study on interaction between LDs and mitochondria and identified several pairs of proteins that may be involved in this interaction (36).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that mitochondria, peroxisomes, ER membranes, and endosomes may be physically associated with LDs (5,34) or may even be continuous with LDs in terms of phospholipid membrane topology (35). Recently, we conducted an interactomic study on interaction between LDs and mitochondria and identified several pairs of proteins that may be involved in this interaction (36).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated LD homeostasis is closely connected to many pathological conditions and the development of various diseases reactive oxygen species (ROS). peroxisome, organelles responsible for lipid oxidation, also have close association with LDs, and Plin5 has been identified to mediate the interaction between LD and mitochondria and may facilitate the transport of FA for oxidative phosphorylation with increased energy demand (Gao and Goodman, 2015;Lodhi and Semenkovich, 2014;Mason and Watt, 2015;Pu et al, 2011;Rambold et al, 2015;Schrader, 2001;Yu et al, 2015). LDs are also observed surrounding the nucleus or actually present in the nucleus that may function to store specific proteins or sequester transcriptional factors Welte, 2015).…”
Section: The Structure and Function Of Ldsmentioning
confidence: 99%
“…ERG6 was shown to be a sterol ⌬ 24 -methy ltransferas ( 97 ) and to mediate the interaction between lipid droplets and mitochondria ( 98 ). Proteomic studies of lipid droplets from another yeast strain, Yarrowia lipolytica , also identifi ed lipid synthetic enzymes and membrane-traffi cking proteins ( 37 ).…”
Section: Plantsmentioning
confidence: 99%